The European integration in criminal field the European arrest warrant - Palmieri Marco (Temida)
The author deals with some thesis in connection with the European arrest warrant experience, what will be an interesting test for many EU countries. It affects prerogatives always reserved to state-power and main expression of national sovereignty. Anyway, bringing up to the theoretical elaboration of the so-called "third pillar", it needs to set them in action, and verify if European states are really willing to create a common juridical space putting apart claims and prejudices. Most of appraisals addressed to European arrest warrant seem to repudiate just the principle of mutual confidence in respective judiciary systems, principle the new form of cooperation is based on. Briefly, they assert a decision issued by another Member State wouldn't assure all guarantees as own juridical system. Reform would surely have been more effective and consistent if, before creating a common procedure substantial rules were set. European arrest warrant was born in order to replace the long and complex extradition system with a quick and effective tool, fit for contrasting new forms of criminality, that are able to profit boundary openings in order to escape justice.